2020
DOI: 10.1037/ser0000327
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cultural identity and attitudes toward routine progress monitoring in a sample of ethnically diverse community therapists.

Abstract: Community mental health services are increasingly embracing evidence-based interventions (EBIs), and the professional workforce is diversifying to meet the needs of historically underserved groups. As such, it is increasingly important to understand how psychotherapist cultural factors may be associated with attitudes toward EBIs. The use of standardized assessments within routine progress monitoring is a cornerstone of EBIs, yet therapist attitudes remain an obstacle to implementation. The current study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Finally, Rodriguez et al (2020) move us to consider MBC implementation from diverse populations, calling us to look at adaptations that may be needed dependent upon the population we serve. They conducted a study of ethnic minority community therapists who were implementing evidence-based psychothera-pies and focused upon assessing therapists' cultural identity and the association of this identity with attitudes toward routine progress monitoring in treatment.…”
Section: Practical Implementation Of Measurement-based Carementioning
confidence: 99%
“…Finally, Rodriguez et al (2020) move us to consider MBC implementation from diverse populations, calling us to look at adaptations that may be needed dependent upon the population we serve. They conducted a study of ethnic minority community therapists who were implementing evidence-based psychothera-pies and focused upon assessing therapists' cultural identity and the association of this identity with attitudes toward routine progress monitoring in treatment.…”
Section: Practical Implementation Of Measurement-based Carementioning
confidence: 99%
“…This study additionally found that identifying as Hispanic/Latinx as compared to Non-Hispanic white significantly predicted less positive attitudes towards measures. A previous study of perceptions of progress monitoring among ethnic minority community therapists who were 69.9% Hispanic found that therapist cultural identity (affiliation to culture of origin) predicted less positive attitudes on the ASA-MF (Rodriguez et al, 2019 ). The present study did not include a measure of cultural identity, but further research should investigate attitudes of ethnic minority therapists towards measures.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the aims of implementation science, which seeks to evaluate the community provision of evidence-based practices, interviews were only conducted with clinicians providing services in community-based settings. Additionally, due to the dearth of information on cultural considerations as they relate to progress monitoring (Rodriguez et al, 2019 ), therapists who provide services in more than one language were oversampled. Twelve participants reported providing services in both English and another language (52.1%), the majority of whom delivered services in both English and Spanish ( n = 9).…”
Section: Methodsmentioning
confidence: 99%
“…Department of Health & Human Services, 2015). Including ethnic minority therapists in the decision-making processes in planning RPM processes and tools can promote both the cultural competence of systems and provider buy-in and adherence to implementation efforts (Clauss-Ehlers et al, 2019; Rodriguez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%